2008
DOI: 10.1177/112067210801800107
|View full text |Cite
|
Sign up to set email alerts
|

Is the PASCAL®-Tonometer Suitable for Measuring Intraocular Pressure in Clinical Routine? Long- and Short-Term Reproducibility of Dynamic Contour Tonometry

Abstract: Short- and long-term reproducibility of DCT is comparable to that of GAT. GAT is more affected by CCT than DCT, measuring higher IOPs in eyes with higher central corneal thickness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…To date, however, few studies have addressed this issue, 4,17,[25][26][27][28][29] and further, to our knowledge, no direct comparisons of variability between these methods within the same group have been reported. This study was thus designed to simultaneously evaluate and compare intraexaminer and interexaminer repeatability, and reproducibility for DCT, ORA, and GAT within the same group of subjects.…”
mentioning
confidence: 81%
“…To date, however, few studies have addressed this issue, 4,17,[25][26][27][28][29] and further, to our knowledge, no direct comparisons of variability between these methods within the same group have been reported. This study was thus designed to simultaneously evaluate and compare intraexaminer and interexaminer repeatability, and reproducibility for DCT, ORA, and GAT within the same group of subjects.…”
mentioning
confidence: 81%
“…Most studies published to date show a good concordance between IOP values measured by PDCT and GAT [18,19].…”
Section: Discussionmentioning
confidence: 75%
“…Ten studies 104,123,129,142,150,155,159,181,210,218 reported on either inter-and/or intraobserver reliability of DCT. The data are shown in Appendix 7.…”
Section: Reliabilitymentioning
confidence: 99%